A chromosome‐scale assembly of the model desiccation tolerant grass Oropetium thomaeum. (15th November 2018) - VanBuren, Robert; Wai, Ching Man; Keilwagen, Jens; Pardo, Jeremy
Abstract: Oropetium thomaeum is an emerging model for desiccation tolerance and genome size evolution in grasses. A draft genome of Oropetium was recently sequenced, but the lack of a chromosome‐scale assembly has hindered comparative analyses and downstream functional genomics. Here, we reassembled Oropetium, and anchored the genome into 10 chromosomes using high‐throughput chromatin conformation capture (Hi‐C) based chromatin interactions. A combination of high‐resolution RNAseq data and homology‐based gene prediction identified thousands of new, conserved gene models that were absent from the V1 assembly. This includes thousands of new genes with high expression across a desiccation timecourse. Comparison between the Sorghum and Oropetium genomes revealed a surprising degree of chromosome‐level collinearity, and several chromosome pairs have near perfect synteny. Other chromosomes are collinear in the gene rich chromosome arms but have experienced pericentric translocations. Together, these resources will be useful for the grass‐comparative genomic community and further establish Oropetium as a model resurrection plant.